Prevalence of low birth weight infants and their association with maternal risk factors: a cross-sectional study - Ivaturi, Sai Deepthi Janaki Rani; Elhussein, Musaab Abdalla; Anireddy, Srivani Reddy; Narayan, Jagadale Pratik (International Journal of Scientific Reports, 2025)
Background: Low birth weight (LBW) remains a major public health issue in developing countries, contributing to neonatal morbidity, mortality, and long-term complications. Identifying maternal risk factors for LBW is essential for preventive strategies. This study aimed to assess the prevalence of LBW and its association with maternal factors in a tertiary care hospital. Methods: A hospital-based cross-sectional study was conducted over three months, including 125 mother-infant pairs. Newborns weighing <2500 grams were classified as LBW. Data were collected through a semi-structured questionnaire covering maternal demographics, antenatal care, health status, and pregnancy complications. Statistical analysis identified associations between maternal factors and LBW. Results: The prevalence of LBW was 33%. Inadequate antenatal visits (<4) were significantly associated with LBW (p=0.0002). Pregnancy complications - anemia, oligohydramnios, and pre-eclampsia - were also strongly linked to LBW (p=0.002). Preterm delivery was a major contributor to LBW (p=0.00001), and poor maternal nutrition was a critical risk factor (p=0.00007). Maternal age (p=0.4), education (p=0.12), and fetal gender (p=0.65) were not significantly associated with LBW. Conclusions: Maternal health, nutrition, and antenatal care significantly influence birth weight. Strengthening prenatal services, early detection of complications, and improving maternal nutrition can reduce LBW prevalence. These findings support the need for targeted maternal and child health interventions to improve neonatal outcomes.